New substitution bases for complexity classes. Issue 1 (23rd December 2019) - Mazzanti, Stefano
Abstract: The set AC 0 ( F ), the AC 0 closure of F, is the closure with respect to substitution and concatenation recursion on notation of a set of basic functions comprehending the set F . By improving earlier work, we show that AC 0 ( F ) is the substitution closure of a simple function set and characterize well‐known function complexity classes as the substitution closure of finite sets of simple functions.